2017
DOI: 10.5191/jiaee.2016.24102
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Factors Influencing Adoption of Agricultural Innovations: Insights from Selected Developing Countries

Abstract: Research has revealed that different factors influence adoption of agricultural innovations by farmers. These factors include characteristics of innovations comprising relative advantage, complexity, compatibility, trialability and observability as discovered by Rogers (1983), and technology characteristics, information sources, knowledge, awareness, attitude, and group influence (Odalele, 2005, p. 250). The diffusion model was considered the main theoretical model for agricultural extension and the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
1
6
0
Order By: Relevance
“…The findings imply that farmers with formal education are likely to be aware of more sources of information and then make informed decisions regarding their farming activities. This assertion confirms the findings of Moyo and Salawu (2016) that the education of farmers influence adoption of agricultural technology in Nigeria. Gender and income level of small ruminant household heads were also tested in the model but did not indicate a statistically significant effect on adoption of husbandry practices.…”
Section: Predicting Factors Of Adoption Of Good Animal Husbandry Pracsupporting
confidence: 90%
“…The findings imply that farmers with formal education are likely to be aware of more sources of information and then make informed decisions regarding their farming activities. This assertion confirms the findings of Moyo and Salawu (2016) that the education of farmers influence adoption of agricultural technology in Nigeria. Gender and income level of small ruminant household heads were also tested in the model but did not indicate a statistically significant effect on adoption of husbandry practices.…”
Section: Predicting Factors Of Adoption Of Good Animal Husbandry Pracsupporting
confidence: 90%
“…When project implementers use CBAM SOC, they become aware of the stages project beneficiaries are in. Knowing this, project leaders can focus on activities that promote lasting adoption and strategically communicate the innovation and thereby, ensure the needs of each farmer are met at the right time (Moyo & Salawu, 2017). Restructuring a project in this way can save time and money.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that influence the acceleration of innovation adoption showed that specifically in different regions, the influencing factors are also very site-specific [7] .…”
Section: Effectiveness Of Innovation Dissemination In Efforts To Incrmentioning
confidence: 99%